Evaluation of the Cortical Silent Period of the Laryngeal Motor Cortex in Healthy Individuals - Chen, Mo; Summers, Rebekah L. S.; Goding, George S.; Samargia, Sharyl; Ludlow, Christy L.; Prudente, Cecília N.; Kimberley, Teresa J. (Frontiers in Neuroscience, 2017)
Objective: This work aimed to evaluate the cortical silent period (cSP) of the laryngeal motor cortex (LMC) using the bilateral thyroarytenoid (TA) muscles with transcranial magnetic stimulation (TMS). Methods: In 11 healthy participants, fine-wire EMG was used to record bilateral TA muscle responses to single pulse TMS delivered to the LMC in both hemispheres. Peripheral responses to stimulation over the mastoid, where the vagus nerve exits the skull, were collected to verify the central origin of the cortical stimulation responses by comparing the latencies. Results: The cSP duration ranged from 41.7 to 66.4 ms. The peripherally evoked MEP peak occurred 5-9 ms earlier than the cortical responses (for both sides of TAs: p<.0001) with no silent period. The right TA MEP latencies were earlier than the left TA responses for both peripheral and cortical measures (p≤.0001). Conclusion: These findings demonstrate the feasibility of measuring cSP of LMC based on intrinsic laryngeal muscles responses during vocalization in healthy volunteers. Significance: The technique could be used to study the pathophysiology of neurological disorders that affect TA muscles, such as spasmodic dysphonia. Further, the methodology has application to other muscles of the head and neck not accessible using surface electrodes.